Membangun Budaya Antikorupsi Pada Remaja Karang Taruna Karya Manunggal di Desa Podang - Prasetyo, Amin; Suyahman, Suyahman; Murtiningsih, Ika (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to describe the anti-corruption culture model for karang taruna Karya Manunggal youth. This research method is descriptive qualitative. The research subjects were youth in Karang Taruna Karya Manunggal in Podang Village, Jumantono District, Karanganyar Regency, while the object of research was anti-corruption culture. Data collection methods used are observation, interviews and documentation. Sources of data obtained through interviews and documentation. The results of the study show that the implementation of an anti-corruption culture has been carried out by Karang Taruna Karya Manunggal youth by habituating their attitudes and behavior, such as. such as being honest in managing funds, being disciplined in paying monthly cash, being responsible for assigned tasks, being fair in implementing the fine system, being brave in expressing opinions in regular meetings, reminding each other in cash payments and caring for members who are sick by visiting them, working hard in the success of the event by being carried out together, simply by selecting each activity or purchasing equipment needs, independently to increase cash income with goats. Whereas the obstacles faced in implementing it are the lack of understanding and awareness of the impact of corruption and low self-confidence in taking an anti-corruption stance.Keywords: anti-corruption culture, youth organizations, youth